Naphthoxy Bounded Ferrocenium Salts as Cationic Photoinitiators for Epoxy Photopolymerization - Zh. Q. Li; M. Li; G. L. Li; Y. Chen; X. N. Wang; T. Wang (International Journal of Photoenergy)
To improve the absorption and the bulk of arene ligands, two naphthoxy bounded ferrocenium salts as new cationic photoinitiators, (η6-α-naphthoxybenzene) (η5-cyclopentadienyl) iron hexafluorophosphate (NOFC-1) and (η6-β-naphthoxybenzene) (η5-cyclopentadienyl) iron hexafluorophosphate (NOFC-2), were synthesized, characterized, and studied. NOFC-1 and NOFC-2 were prepared by the reaction of nucleophilic substitution (SNAr) with naphthol and chlorobenzene-cyclopentadienyliron salt. Their activity as cationic photoinitiators was studied using real-time infrared spectroscopy. The results obtained showed that NOFC-1 and NOFC-2 are capable of photoinitiating the cationic polymerization of epoxy monomer directly on irradiation with long-wavelength UV light (365 nm). Comparative studies also demonstrated that they exhibited better efficiency than cyclopentadienyl-Fe-cymene hexafluorophosphate (I-261). When NOFC-1 and NOFC-2 were used to efficiently initiate polymerization of epoxide, both rate of polymerization and final conversion increased using benzoyl peroxide (BPO) as sensitizer. DSC studies showed that NOFC-1 and NOFC-2 photoinitiators in epoxides possess good thermal stability in the absence of light.